Repercussions of patrilocal residence on mothers' social support networks among Tsimane forager–farmers. (16th January 2023) - Seabright, Edmond; Alami, Sarah; Kraft, Thomas S.; Davis, Helen; Caldwell, Ann E.; Hooper, Paul; McAllister, Lisa; Mulville, Sarah; von Rueden, Christopher; Trumble, Benjamin; Stieglitz, Jonathan; Gurven, Michael; et al.
Abstract : While it is commonly thought that patrilocality is associated with worse outcomes for women and their children due to lower social support, few studies have examined whether the structure of female social networks covaries with post-marital residence. Here, we analyse scan sample data collected among Tsimane forager–farmers. We compare the social groups and activity partners of 181 women residing in the same community as their parents, their husband's parents, both or neither. Relative to women living closer to their in-laws, women living closer to their parents are less likely to be alone or solely in the company of their nuclear family (odds ratio (OR): 0.6, 95% CI: 0.3–0.9), and more likely to be observed with others when engaging in food processing and manufacturing of market or household goods, but not other activities. Women are slightly more likely to receive childcare support from outside the nuclear family when they live closer to their parents (OR = 1.8, 95% CI 0.8–3.9). Their social group size and their children's probability of receiving allocare decrease significantly with distance from their parents, but not their in-laws. Our findings highlight the importance of women's proximity to kin, but also indicate that patrilocality per se is not costly to Tsimane women. This article is part of the theme issue 'Cooperation among women: evolutionary and cross-cultural perspectives'.